Unravelling biogeochemical drivers of methylmercury production in an Arctic fen soil and a bog soil. (15th April 2022) - Zhang, Lijie; Philben, Michael; Taş, Neslihan; Johs, Alexander; Yang, Ziming; Wullschleger, Stan D.; Graham, David E.; Pierce, Eric M.; Gu, Baohua
Abstract: Arctic tundra soils store a globally significant amount of mercury (Hg), which could be transformed to the neurotoxic methylmercury (MeHg) upon warming and thus poses serious threats to the Arctic ecosystem. However, our knowledge of the biogeochemical drivers of MeHg production is limited in these soils. Using substrate addition (acetate and sulfate) and selective microbial inhibition approaches, we investigated the geochemical drivers and dominant microbial methylators in 60-day microcosm incubations with two tundra soils: a circumneutral fen soil and an acidic bog soil, collected near Nome, Alaska, United States. Results showed that increasing acetate concentration had negligible influences on MeHg production in both soils. However, inhibition of sulfate-reducing bacteria (SRB) completely stalled MeHg production in the fen soil in the first 15 days, whereas addition of sulfate in the low-sulfate bog soil increased MeHg production by 5-fold, suggesting prominent roles of SRB in Hg(II) methylation. Without the addition of sulfate in the bog soil or when sulfate was depleted in the fen soil (after 15 days), both SRB and methanogens contributed to MeHg production. Analysis of microbial community composition confirmed the presence of several phyla known to harbor microorganisms associated with Hg(II) methylation in the soils. The observations suggest that SRB and methanogens were mainly responsible for Hg(II) methylation in these tundra soils, although their relative contributions depended on the availability of sulfate and possibly syntrophic metabolisms between SRB and methanogens. Graphical abstract: Image 1 Highlights: Biogeochemical drivers of mercury methylation in Arctic tundra soils were investigated. Sulfate-reducing bacteria and methanogens are main contributors to methylmercury production. Sulfate promotes methylmercury production in the low-sulfate tundra soils. Results shed new light on mercury methylation in the Arctic ecosystem under warming.